2022
DOI: 10.1007/s10067-022-06343-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intervention on cardiorespiratory fitness in rheumatoid arthritis patients with high cardiovascular disease risk: a single-arm pilot study

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although exercise prescription for RA was traditionally controversial because of fear that excessive exercise would worsen joint disease, more recent research has shown instead that exercise training for RA is overall safe and confers many health benefits ( 56 , 57 , 58 ). Exercise training programs impact traditional CVD risk factors by improving RA aerobic fitness, blood pressure, lipid profiles, and body composition (ie, increased muscle mass, decreased fat mass) ( 59 , 60 , 61 , 62 , 63 ). Exercise training also improves RA inflammatory CVD risk factors.…”
Section: The Effect Of Exercise Training On Ra Cvd ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although exercise prescription for RA was traditionally controversial because of fear that excessive exercise would worsen joint disease, more recent research has shown instead that exercise training for RA is overall safe and confers many health benefits ( 56 , 57 , 58 ). Exercise training programs impact traditional CVD risk factors by improving RA aerobic fitness, blood pressure, lipid profiles, and body composition (ie, increased muscle mass, decreased fat mass) ( 59 , 60 , 61 , 62 , 63 ). Exercise training also improves RA inflammatory CVD risk factors.…”
Section: The Effect Of Exercise Training On Ra Cvd ...mentioning
confidence: 99%
“…Both traditional aerobic/cardio training and resistance/strength training individually improve RA disease activity and systemic inflammation ( 64 , 65 , 66 , 67 ). Moreover, combined aerobic and resistance exercise training programs may potentially improve RA disease activity to a greater extent than either modality alone ( 59 , 63 , 68 ). Our previous work also shows that high‐intensity interval exercise training improves RA disease activity, markers of inflammation (ie, erythrocyte sedimentation rate [ESR]), as well as neutrophil migration and monocyte phagocytosis ( 60 ).…”
Section: The Effect Of Exercise Training On Ra Cvd ...mentioning
confidence: 99%
“… 89 It improves the cardiorespiratory fitness and disease activity in RA patients with a risk for CVD. 90 , 91 Psychotherapy helps to improve self-confidence and regaining positive attitude to cope with the depression and associated comorbidities in patients. 92 …”
Section: Treatment Strategiesmentioning
confidence: 99%